(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The aim of the study is to analyze the theoretical basis of creative economy and its development trends in the context of innovative business ecosystems formation. The scientific novelty of the research consists in solving the most important scientific and applied problem - further development of theoretical provisions of creative economy, ecosystems, as well as substantiation of the conceptual approach to the formation of innovative business ecosystem as a coherent management model. In the process of research, general scientific and special methods were used: scientific abstraction, deduction, analysis and synthesis, system and critical analysis, structural-logical, ascending from the abstract to the concrete, and statistical analysis. It has been substantiated that the priority development of creative economy as a strategic driver of sustainable development is the formation of an ecosystem conducive to the development of complex non-linear dynamic innovation processes, development of value propositions and value chain. The analysis of theoretical and methodological aspects of formation and functioning of ecosystems indicates the lack of development of this problem and the need to develop scientific approaches to their identification. Generalization of the results of theoretical analysis allowed us to group ecosystems according to the identified attributes into five main types. It was substantiated that a sustainable business ecosystem is a favorable environment for innovation to increase its value and contribute to the achievement of sustainable development goals. It is proposed to consider a sustainable "business ecosystem" as a coherent management model with established characteristics, which describes an aggregate system of business ecosystem modules that interact with each other and are focused on co-creation and co-production of value.